Magnus : queer news, opinions and culture. (San Francisco : Magnus-Hirschfeld-Gesellschaft, 1999)
Fonds Suzan Daniel (FSD)
Periodiciteit: maandelijks
Redactie: 2215-R Market Street 495, San Francisco CA 94114
Engels
Periodiek